Methodology for Assessing Enterprises’ Maturity to Use Open Data - Kljajić Borštnar, Mirjana; Rajkovič, Uroš; Blatnik, Staša; Pucihar, Andreja (Odprti podatki kot pospeševalec družbenih, okoljskih in gospodarskih inovacij – priložnosti in izzivi, 2026)
Open data (OD) has emerged as a key driver of transparency, innovation, and economic growth. Although governments have made substantial investments in OD infrastructure, the actual use and integration of OD within enterprises remain limited and insufficiently studied. To encourage the adoption of open data in businesses, it is first necessary to understand which capabilities an enterprise must develop to effectively utilize OD in its operations, and then to assess the achievement of these capabilities, i.e., its maturity for OD use. To this end, we developed a comprehensive methodology for measuring OD maturity in Slovenian enterprises, using a multi-criteria decision model based on the DEX methodology. The model was implemented as an online self-assessment tool and tested in practice. The methodology contributes to a better understanding of OD adoption in enterprises and provides practical insights and recommendations that are also relevant for policymaking and for fostering further development of data-driven innovation in the private sector.